Volitional self-regulation and emotional burnout of professional sambo-athletes who suffered from sports injuries - D. R. Mikov; V. G. Cherkasova; S. V. Muravev; P. N. Chainikov; A. M. Kulesh (National Electronic Information Consortium (NEICON), 2020)
Objective: to study the level of volitional self-regulation and emotional burnout in male sambo-athletes who underwent sports injuries of various degrees of severity. Materials and methods: 60 male sambo-athletes were examined. They were divided into 3 groups of 20 people in each group based on types of sports injuries. Results: significantly (p=0.001) lower level of volitional self-regulation was found in the third group who underwent more injuries (total scale: Q1=6,0; Me=8,0; Q3=10,0; «perseverance»: Q1=5,0; Me=5,5; Q3=8,0; «self-control»: Q1=4,0; Me=4,5; Q3=5,0). More pronounced emotional burnout occured in athletes who had more injuries (Q1=64,5; Me=69,0; Q3=71,0; p=0,001). Inadequate emotional response and emotional and moral disorientation was leveled down with aggravation of the severity of injuries (Q1=25,0; Me=44,0; Q3=61,0; p=0,039). Adaptation systems strain is manifested by a marked emotional exhaustion and decrease in volitional self-regulation with an increase in the number of injuries. Conclusions: if incidence and severity of injuries increases in sambo-athletes the level of volitional self-regulation reduces and emotional burnout occurs, which is characterized by the stress of the system of psychological adaptation.